Why Some Films are Never Boring? - Marqueta Calvo, Sergio (Analysis. Journal of Philosophical Research, 2022)
Taking the question that heads these lines as our starting point this article analyzes what takes place in the cinematographic experience beyond those typical responses of the cognitivist theory which only considers the narration and its reception by a cogito. To that end, and taking into account the affective turn, an ontological trip will be carried out that will address the particularities, differences and connections between these three dimensions; the affective space or the open material totality, the inhabited worlds or those series of rules that cut and stabilize the affective space, and the different narrations as concretions of such worlds.